Enhancing Energy Efficiency of Hydrodealkylation (HDA) Toluene for Benzene Production through Optimizing Utility Tool (Pinch Analysis) - Pardede, Audrey Olivia Adlai; Itsnainie, Izzah Nabila; Fazila, Sanandha Azwa; Kamila, Sinta (UPT Laboratorium Terpadu, Universitas Diponegoro, 2024)
Benzene is one of the chemicals widely used in domestic and industrial products. There have been many extensive studies conducted on hydrodealkylation processes to produce benzene from toluene to achieve the optimum result. Aspen hysys V.11 used to simulate hydrodealkylation process. In this study, this work aims to optimize energy efficiency and manage the heat generated by the highly exothermic hydrodealkylation reaction by adjusting the utility type of the heater and cooler. The results of the analysis and calculations, the utility modifications in the heat exchanger network system have proven to have a positive impact on energy efficiency and overall performance. With high energy efficiency, the system is able to reduce reliance on auxiliary utilities while improving the sustainability of the production process. This approach is not only beneficial from an operational perspective but also contributes significantly to cost savings and reduced environmental impact, making it a very viable solution to implement. Copyright © 2024 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).